Cardiorenal Fat: A Cardiovascular Risk Factor With Implications in Chronic Kidney Disease - D'Marco, Luis; Puchades, María Jesús; Panizo, Nayara; Romero-Parra, María; Gandía, Lorena; Giménez-Civera, Elena; Pérez-Bernat, Elisa; Gonzalez-Rico, Miguel; Gorriz, José Luis (Frontiers in Medicine, 2021)
There is a growing interest in the potential role of adipose tissues on cardiac and renal pathophysiology. Thus, it is of clinical concern to determine the mechanisms by which fat compartments around the heart and kidneys influence on cardiovascular disease (CVD) in general and high-risk populations. Thus, epicardial fat (EF) and perirenal fat (PF) has been associate with adverse outcomes in chronic kidney disease (CKD) patients. EF it is a rich source of free fatty acids and it is capable of secreting inflammatory and pro-atherogenic cytokines that promote atherosclerosis through a local paracrine effect. Recent evidence demonstrated that PF have a closer association with kidney diseases rather than other visceral fat deposits in obesity or metabolic disturbances. Moreover, PF has been linked as independent risk factor for CKD progression and even associated with cardiorenal dysfunction. In these regard, these forms of organ specific fat deposits may act as connection of vascular and cardiorenal disease. This review explores the possible links between epicardial and PF and its significant role as a modulator of cardiorenal dysfunction in CKD patients.